PENGEMBANGAN ASESMEN DIAGNOSTIK BERBASIS MEDIA GOOGLE FORM DI MAN MODEL 1 MANADO - Motulo, Serlin J; Mokosuli, Yeremia S; Kamagi, Decky W. (LPPM Politeknik Saint Paul Sorong, 2024)
Serlin J. Motulo, 20 507 023. Development of a diagnostic assessment based on Google Form Media in MAN Model 1 Manado. Thesis, Department of Biology, Faculty of Mathematics, Natural and Earth Sciences, State University of Manado. Tondano. 2024. Supervisor Prof. Dr. Yermia S. Mokosuli, M.Si and Dr. Decky W. Kamagi, M.Sc. This research is motivated by teachers who did not maximize diagnostic assessments due to a lack of understanding and limited time spent creating, applying and analyzing data. This research aims to develop a diagnostic assessment that is effective, efficient, easy to perform and economical. This research is a developmental research using the ADDIE model which includes five stages, namely analysis, design, development, implementation and evaluation. According to the research results on products developed by media experts, the percentage obtained was 97.1% (very achievable). Then for the evaluation experts, the percentage obtained is 100% (very achievable). Moreover, materials experts, the percentage obtained was 98.75% (very feasible). Meanwhile, the test results for subject teachers' responses obtained a percentage of 97.3% (very feasible) and the average percentage of student responses was 91.8% (very feasible). The development of diagnostic assessments based on Google Forms materials is very suitable for carrying out assessments that can be carried out both online and offline